Oil based nano-emulsion formulation of azadiracthin for biopesticide - Omar, Dzolkhifli; Basri, Mahiran; Muhamad Awang, Rita; Kamarudin, Noorhazwani (2013)
A broad spectrum plant based formulation for killing insects includes an active ingredient extracted from a plant material, a surfactant in an effective amount to provide emulsification of the formulation and reducing surface tension of the formulation and a carrier for the active ingredient, the carrier includes an insecticidal oil-containing amide.